Antibiotic use by poultry farmers in Kiambu County, Kenya: exploring practices and drivers of potential overuse - Jeniffer Waiyego Kariuki; Jan Jacobs; Marie Paule Ngogang; Olivia Howland (Antimicrobial Resistance and Infection Control, 2023)
Abstract Background Antibiotic resistance is a global concern threatening achievements in health care since the discovery of antibiotics. In Kenya, this topic remains understudied in a context of rising demand for livestock products, intensification and the concomitant increase in antibiotic use. Our study investigates drivers and practices of antibiotic use in poultry farming. The study was conducted in Kiambu County, Kenya. Methods A qualitative research methodology was employed: fourteen key informant interviews, twenty in-depth interviews, and four focus group discussions were undertaken. The interviews were semi-structured. Themes and subthemes from the interviews were generated through inductive analysis. Findings Of the farmers interviewed, sixty eight percent were female, thirty three percent of the sampled farmers could not read, and the majority (eight five percent) of farmers had reared poultry for at least ten years. Research findings showed that farmers extensively used antibiotics. Antibiotic use was influenced by factors such as high disease burden, access to medicines and economic pressure. Common practices included prophylactic use, use of antibiotics to enhance production, self-prescription use, use of combination antibiotics (A combination antibiotic is one in which two or more antibiotics are added together for additional therapeutic effect.), and antibiotics classified as critically important in human medicine. Key information sources for the farmers were agro- veterinary dispensers, sellers of day-old chicks, and peer-learning. External factors driving the inappropriate use of antibiotics included access to the antibiotics, influence by marketers such as sellers of day-old chicks, and branding. Use of antibiotics was also driven by economic factors among the farmers, sellers of day-old chicks and agro-veterinary dispensers. Conclusions Our findings indicate widespread use of antibiotics among poultry farmers in our study site. The use of antibiotics is influenced by an interplay of issues at the farmers’ level as well as broader social, economic and structural level factors. A multifaceted One Health approach focusing on regulatory frameworks, knowledge transfer, and research is required to promote stewardship and judicious use of antibiotics.